2013
DOI: 10.1056/nejmoa1308789
|View full text |Cite|
|
Sign up to set email alerts
|

Thrombus Aspiration during ST-Segment Elevation Myocardial Infarction

Abstract: Routine thrombus aspiration before PCI as compared with PCI alone did not reduce 30-day mortality among patients with STEMI. (Funded by the Swedish Research Council and others; ClinicalTrials.gov number, NCT01093404.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
705
6
24

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,012 publications
(762 citation statements)
references
References 28 publications
27
705
6
24
Order By: Relevance
“…This conclusion is confirmed by the neutral results of the TASTE (n=7244) and TOTAL (n=10 732) trials, both of which were specifically designed to reliably detect differences in clinical outcomes. 7,8 The findings of TOTAL are also consistent with the Intracoronary Abciximab and Aspiration Thrombectomy in Patients with Large Anterior Myocardial Infarction (INFUSE AMI) trial, 26 which showed no difference in infarct size with routine thrombus aspiration.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…This conclusion is confirmed by the neutral results of the TASTE (n=7244) and TOTAL (n=10 732) trials, both of which were specifically designed to reliably detect differences in clinical outcomes. 7,8 The findings of TOTAL are also consistent with the Intracoronary Abciximab and Aspiration Thrombectomy in Patients with Large Anterior Myocardial Infarction (INFUSE AMI) trial, 26 which showed no difference in infarct size with routine thrombus aspiration.…”
Section: Discussionsupporting
confidence: 60%
“…7 However, TASTE was a registrybased trial that relied on discharge diagnosis codes without adjudication. Moreover, in the TAPAS trial, stroke was not a prespecified outcome and was not reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is still much debate about the utility of routine usage of thrombus aspiration catheters in STEMI patients. Some recent studies demonstrated that routine usage of this device may not improve mortality or bring any advantages in that field [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…As long as the registry is capable of identifying patients with a partial hip revision, the concept of the registryembedded study [5] is probably the most-realistic tool for getting answers regarding the efficacy of partial hip revision in PJI. In registry-embedded studies, both an observational design and a randomization design [10] are possible.…”
Section: How Do We Get There?mentioning
confidence: 99%